2018
DOI: 10.1111/phen.12263
|View full text |Cite
|
Sign up to set email alerts
|

The secreted salivary proteome of Asian citrus psyllid Diaphorina citri

Abstract: The Asian citrus psyllid Diaphorina citri Kuwayama is a sap‐sucking hemipteran that serves as a vector for Candidatus Liberibacter asiaticus (CLas), the causal agent of citrus huanglongbing (HLB). Salivary secretions play critical roles in insect–host plant interactions and are responsible for the establishment of insect herbivory. In the present study, we aim to identify the major proteins in D. citri saliva. Saliva proteins are collected from the artificial diet upon D. citri feeding. Collected proteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Despite the existence of the ACP saliva proteome 33 , ACP effectors or salivary molecules that interact with host plants have not been identified until now 34 . In the present work, we predict secreted D. citri effectors using bioinformatics tools.…”
mentioning
confidence: 99%
“…Despite the existence of the ACP saliva proteome 33 , ACP effectors or salivary molecules that interact with host plants have not been identified until now 34 . In the present work, we predict secreted D. citri effectors using bioinformatics tools.…”
mentioning
confidence: 99%
“…In addition, cathepsin is a cysteine protease and functions as a primary digestive enzyme to degrade host defense proteins. It is common in the watery saliva of Diuraphis noxia (Nicholson et al, 2012), N. lugens (Liu et al, 2016) and D. citri (Yu and Killiny, 2018). Our results showed that six cathepsins with signal peptides were significantly changed (one upregulated and five downregulated) in CLas-infected D. citri.…”
Section: Discussionmentioning
confidence: 62%
“…Compared with these studies, we identified slightly more proteins in the SG of D. citri, and our data provide valuable information for further study of functional protein activity in the SG. In addition, 86 saliva proteins were identified from D. citri via an LC-MS/MS analysis (Yu and Killiny, 2018). More proteins were obtained from the SG than from the gathered saliva in D. citri.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations